Introducing environmental-justice analysis into urban planning practices in the city of Bottrop, Germany. Issue 2 (1st March 2022) - Ohlmeyer, Kristina; Schaefer, Mathias; Kirstein, Madeleine; Gruehn, Dietwald; Greiving, Stefan
Abstract : An analysis of the provision and accessibility of urban green infrastructure was carried out and combined with the spatial exposure of social-welfare recipients to noise, air pollution and weather extremes in the city of Bottrop, Germany. We found out that social-welfare recipients tend to live in areas where the exposure to multiple environmental burdens is higher compared to other statistical districts in the city. Ultimately, there is a real impact of our conceived indicators, since they were integrated into an obligatory 'sustainability check', which was adopted by the city assembly of Bottrop in June 2020.